THE DEVELOPMENT OF HUMAN CAPITAL FOR THE HALAL INDUSTRY: ISLAMIC MANAGEMENT PERSPECTIVE - Abdus Salam Dz; Eti Nurhayati (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
The basic resource of activity in every industry is humans. The most successful industry managers are those who manage human capital effectively and efficiently. The halal industry must be truly halal in its inputs, processes and products. Because of that, productive Islamic human capital is needed in managing the halal industry. This study aims to: (1) offer an understanding of the importance of Islamic human capital productivity management, (2) discuss the pattern of developing productive human capital in the management of the halal industry. This study uses qualitative analysis of various related literature, so as to produce a normative description. The results of the study concluded: (1) managing the halal industry required Islamic human capital productivity, (2) in its development needed a management pattern derived from Islamic teachings.